MODERN ASPECTS OF RADIATION DIAGNOSIS OF CERVICAL CANCER - Dubininа V.; Lukyanchuk, A.V.; Demidovа E.A. (World of Medicine and Biology, 2015)
Background: The possibility of a comprehensive survey of radiation diagnosis of patients with advanced cervical cancer has been studied for the first time on a large clinical material. Ultrasound, CT, MRI - semiotics of invasive cervical cancer, according to the stages of the pathological process have been developed. The role of the current methods of radiation survey in determining the prevalence of cancer has been clarify. The possibilities of ultrasound , CT, MRI in the evaluation of primary tumor focus, invasion of cervical cancer in the vagina and uterine body, spread of tumors to parametrial tissue, bladder and rectum have been studied. A comparative analysis of the information content of the ultrasound, CT and MRI in the diagnosis of specific lesions and retroperitoneal lymph node involvement in the pathological process of the urinary system. The significance of diagnostic imaging approaches in the evaluation of the effectiveness of treatment for cervical cancer has been identified. The radiation pattern of complete and partial remission, stabilization, as well as progression of the disease has been studied in detail. Material and methods: The research is based on a survey of 120 patients with advanced cervical cancer. Diagnosis of the disease in all cases was verified histologically. Age of 66.6% of all patients accounted for 4-5 decades of life. The majority of the examinees had stage III cervical cancer (66.7%), double-sided version of the parametrium (56%), mixed form of tumor growth (57.5%). Non-keratinizing squamous-cell cancer (44.2%) prevailed according to the histological structure. Results: the radial semiotics according to the stages of the disease was formulated, the developed clear MRI / CT - criteria give characteristic of infiltration of parametrial tissue, tumor invasion into the bladder and rectum, the spread of tumors in the body of the uterus and vagina. Conclusions: on the basis of the results the algorithm of ultrasound examination was formulated, practical recommendations for gynecologists were developed.